DAMPAK PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL TERHADAP PEMBENTUKAN JATI DIRI SISWA: SYSTEMATIC LITERATURE REVIEW - Eka Setiahati; Ida Mirna; Tri Agustina M; Mutoharoh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of globalization and modernization has brought significant changes to the Indonesian education system, particularly in shaping students’ character and identity. Alongside these changes, concerns have emerged regarding the weakening of local cultural values and students’ identity formation. This study aims to systematically review empirical research on the impact of character education based on local wisdom on the formation of students’ identity in Indonesia. This research employed a Systematic Literature Review (SLR) approach by following the PRISMA 2020 guidelines. Relevant studies were collected from national and international databases, including Garuda, Neliti, Google Scholar, and institutional repositories, with publications ranging from 2018 to 2025. The selected studies were analyzed narratively and thematically to identify patterns, impacts, and methodological trends. The findings indicate that character education based on local wisdom has a positive impact on students’ identity formation, particularly in strengthening cultural identity, social attitudes, moral values, and responsible behavior. The internalization of local values occurs through contextual learning, habituation, teacher role modeling, and community involvement. However, the review also reveals methodological limitations in previous studies, including limited sample sizes, non-experimental designs, and insufficient standardized measurement instruments. Overall, this study concludes that character education based on local wisdom is a strategic and contextual approach to strengthening students’ identity and character in Indonesian education, while emphasizing the need for more rigorous and comprehensive future research. Keywords: character education, local wisdom, student identity, systematic literature review